The influence of the oxidation method on the properties of reduced graphene oxide - Drewniak, Łukasz; Drewniak, Sabina (Photonics Letters of Poland, 2022)
Derivatives of graphene have become important materials due to their excellent properties. Graphene oxide and reduced graphene oxide are especially interesting because they are produced relatively easily, cheaply and quickly. Among many possible applications, reduced graphene oxide is a good candidate for sensor applications. Its properties can be controlled at the production stage. The precursor used and the method of oxidation have a significant influence on its properties. Therefore, it is worth take a closer look at them. In this paper we analyse the influence of the oxidation method on the size of the reduced graphene stock which determine the sensitivity of the rGO layer. We used AFM microscopy for this purpose. Full Text: PDF References S.M. Majhi, A. Mirzaei, H.W. Kim, S.S. Kim, "Reduced Graphene Oxide (rGO)-Loaded Metal-Oxide Nanofiber Gas Sensors: An Overview", Sensors 21, 4 (2021). CrossRef M. Pumera, "Graphene-based nanomaterials for energy storage", Energy Environ. Sci. 4 3 (2011). CrossRef X. Yu, H. Cheng, M. Zhang, Y. Zhao, L. Qu, G. Shi, "Graphene-based smart materials", Nat. Rev. Mater. 2, 9 (2017). CrossRef M.Y. Xia, Y. Xie, C.H. Yu, G.Y. Chen, Y.H. Li, T., Zhang, Q. Peng, "Graphene-based nanomaterials: the promising active agents for antibiotics-independent antibacterial applications", J. Control. Release 10 (2019). CrossRef X. Zhu, Y. Zhou, Y. Guo, H. Ren, C. Gao, "Nitrogen dioxide sensing based on multiple-morphology cuprous oxide mixed structures anchored on reduced graphene oxide nanosheets at room temperature", Nanotechnology 30 45 (2019). CrossRef Z. Wu, Y. Wang, S. Ying, M. Huang, C. Peng, "Fabrication of rGO/Cuprous Oxide Nanocomposites for Gas Sensing", IOP Conf. Ser.: Earth Environ. Sci. 706, 1 (2021). CrossRef S. Pei, H.M. Cheng, "The reduction of graphene oxide", Carbon 50, 9 (2012). CrossRef K. Spilarewicz-Stanek, A. Kisielewska, J. Ginter, K. Bałuszyńska, I. Piwoński, "Elucidation of the function of oxygen moieties on graphene oxide and reduced graphene oxide in the nucleation and growth of silver nanoparticles", RSC Adv. 6, 65 (2016). CrossRef R. Muzyka, S. Drewniak, T. Pustelny, M. Sajdak, Ł. Drewniak, "Characterization of Graphite Oxide and Reduced Graphene Oxide Obtained from Different Graphite Precursors and Oxidized by Different Methods Using Raman Spectroscopy Statistical Analysis", Materials 14, 4 (2021) CrossRef B. Lesiak, G. Trykowski, J. Tóth, et al. "Chemical and structural properties of reduced graphene oxide—dependence on the reducing agent", J Mater. Sci. 56 (2021). CrossRef .